Federal Appellate Court Allows Hungarian Holocaust Survivors to Pursue Claims. Issue 2 (9th April 2019) - Unknown
Abstract : On December 28, 2018, the Court of Appeals for the District of Columbia Circuit held in Simon v. Republic of Hungary that fourteen Hungarian Jewish survivors of the Holocaust could continue to pursue their claims against Hungary and its state-owned railway. In a 2–1 decision authored by Judge Millett, the D.C. Circuit reversed the district court decision that had dismissed the case on two alternative grounds—the principle of international comity and the doctrine of forum non conveniens . The D.C. Circuit thus remanded the long-running case for further proceedings.